Social media, legacy media and gatekeeping: the protest paradigm in news of Ferguson and Charlottesville. Issue 3 (3rd July 2019) - Ismail, Amani; Torosyan, Gayane; Tully, Melissa
ABSTRACT: This study investigates the site of intersection between legacy and social media, whereby it asks how local legacy media (St Louis Post-Dispatch and Richmond Times-Dispatch) invoked social media (Facebook and Twitter) discourse within their coverage of the Ferguson (2014) and Charlottesville (2017) events. It thus explores how gatekeeping is manifested and, consequently, how the protest paradigm emerged in a news landscape of proliferating social media. Thematic textual analysis indicates that coverage of Charlottesville and Ferguson clearly relied on indulging the social media sphere in important ways. Common themes of social media as multipurpose platforms, as interfacing with law and order, and as reconciling material and digital modes culminating in social activism were revealed. The study shows that the protest paradigm that has long characterized legacy media's coverage of social protest is not as "pure" as it may once have been, since a social media component is helping define the contours and content of legacy media's landscape.